Cooperative driver stress sensing integration with eCall system for improved road safety - Urbano, Margarida
Understanding drivers' behavior under various challenging situations, to avoid accidents, is considered a key research area in the field of safety for Intelligent Transportation System (ITS). Various events (stressors) occurring while driving vehicles may negatively impact drivers' ability to detect and react to unpredictable incident that can possibly cause accidents. A cooperative stress detection system, in which drivers stress levels are continuously monitored and anonymously disseminated to other vehicles and to roadside units (RSUs), may contribute to the early detection of potentially dangerous situations and road's critical sections, thus increasing road safety. Therefore, this paper presents an experimental assessment on the feasibility of such visionary system. For this purpose, we estimate the driver emotional state relying on previously identified user emotional profiles and stress modeling techniques. The envisioned cooperative stress detection system is integrated with eCall system and vehicular communications based on the IEEE 802.11p/ETSI ITS G5, to communicate with on-board units (OBU) of other vehicles and roadside units (RSU). The eCall system is mainly used to inform the public health authorities and ensure on-time medical assistance. Real-world tests, consisting six drivers and two different cities, are performed to validate the functionality of the proposed system.